About structured questions and reliable answers in abuse and dependency care - a reliability study of the interview method DOK - Dahlberg, Mikael; Anderberg, Mats (Linnaeus University, 2009)
In 1994 a project in abuse and addiction care was initiated in Sweden - DOC. The project, which began in 1991, was inspired by other documentation systems in Sweden, Europe and USA. The aim was to initiate quality- and method development on a scientific basis.
The reliability of self-reported drug use, an aspect which is often discussed, may vary between different populations and situations. The study was conducted to evaluate the reliability, for the stability of the data collected by the DOC's interview method. The data set includes data collected with this method at two different interview occasions.

Purpose:

The main was that interviews with clients should provide a better basis for judgments and decisions about different interventions. Another objective was that the data also may be the basis for evaluation and research activities, and for national and international comparisons.

Under år 1994 inleddes ett projekt inom missbruks- och beroendevården i Sverige - DOK. Utvecklingsarbetet, som påbörjades 1991, var inspirerat av andra dokumentationssystem i Sverige, övriga Europa och USA. Syftet var att initiera kvalitets- och metodutveckling på en vetenskaplig grund.
Tillförlitligheten i självrapporterad droganvändning, en aspekt som är föremål för diskussion, kan variera betydligt mellan olika populationer och situationer. Studien gjordes föra att värdera reliabiliteten, avseende stabiliteten i uppgifter inhämtade med DOK:s inskrivningsintervju. Datasetet innehåller uppgifter inhämtade med intervjumetoden vid två olika intervjutillfällen.

Syfte:

Huvudsyftet har varit att strukturerade intervjuer med klienter ska utgöra en bättre grund för bedömningar och beslut om olika interventioner. Ett annat syfte var att den samlade dokumentationen också kan ligga till grund för utvärderings- och forskningsaktiviteter samt för nationella och internationella jämförelser.
Om strukturerade frågor och tillförlitliga svar i missbruks- och beroendevård - en reliabilitetsstudie av intervjumetoden DOK
Keywords: Alcohol Drinking; Alkoholkonsumtion; Alcohol-Related Disorders; Alkoholmissbruk; Behavior, Addictive; Missbruksbeteende; Health Services Research; Hälso- och sjukvårdsforskning; Methods; Metoder; Substance-Related Disorders; Missbruksrelaterade sjukdomar; Reproducibility of Results; Resultatets reproducerbarhet; Smoking; Rökning; Statistics as Topic; Statistik som ämne; Drug Users; Drogmissbrukare; HEALTH; HÄLSA; Medical and Health Sciences; Medicin och hälsovetenskap; Diet and nutrition; Kost och näring